The relationship between macroeconomic variable and stock price (KLSE-CI) / Siti Mariani Mohd Ariffin (Faculty of Business and Management, 2007)
The Kuala Lumpur Stock Exchange Composite Index is a broad-based capitalizationweighted index of 100 stocks designed to measure the performance of the Kuala Lumpur Stock Exchange. It is important to measure the general and overall performance of the Malaysia stock market From the KLCI, we can predict how the general movement of the KLCI price at KLSR The purpose of this study is to analyze the relationship between KLCI with money supply, exchange rate, external reserves and inflation rate (CPI). Sample data of KLCI were taken on the monthly basis for nine years over the period 1997 to 2005. The regression analysis was used as a tool in interpreting and analyzing data. From the t-statistic result, it is concluded that three variable are significant which are money supply, exchange rate and external reserves. For the interest rate (CPI), it is not significant because the t-statistic is lower than Ta (1.268). Several recommendations are given based on finding and analysis of this study in order to improve the result for the next research paper.